Decoding Style: A Stylistic Analysis of Non-Literary Texts (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the stylistic intricacies present in non-literary texts,  ranging from advertisements and news articles to business reports and social media  posts. The author explores how linguistic choices influence persuasion, clarity in  informational texts, the tone of business communication, the harmony of visual and verbal elements in multimedia presentations, the impact of syntax in social media  discourse, and the role of cultural nuances in global communication. The article  successfully highlights the significance of stylistic analysis in non-literary texts,  shedding light on the diverse strategies employed in different communication genres. The examples and categories presented provide a comprehensive understanding of how  language choices contribute to the effectiveness of communication